The Relative Effectiveness of Various Instructional Approaches During the Performance and Learning of Motor Skills. Issue 1 (2nd January 2016) - Gredin, Viktor; Williams, A. Mark
ABSTRACT: The authors examined the relative effectiveness of explicit internal-oriented instructions, explicit external-oriented instructions, and unguided discovery learning on the performance, acquisition, and learning of a motor skill using novice youth soccer players. Thirty-seven players (age = 9.9 ± 0.7 years) underwent 3 × 30 trials of instruction-specific blocks of practice. The accuracy of lofted soccer kicks was assessed under practice conditions (prior to and after the practice period and after each practice block) and transfer conditions (prior to and after the practice period). Our findings indicated that generalized explicit instructions have detrimental effects on performance, whereas the benefits of unguided discovery learning increase with the amount of practice undertaken and when performing under transfer conditions.